Export Market Orientation as Mediation between Entrepreneurial Orientation and Learning Orientation on Export SME Performance - Raharja, Indra; Hamdan, Hamdan; Kurniawan, Deden (Dinasti Publisher, 2024)
This research is about the role of Export Market Orientation as mediation of Entrepreneurship Orientation and Learning Orientation on Export SME Performance in Indonesia. The main phenomenon is the total contribution of non-oil and gas exports (SMEs) which has a tendency to stagnate or even decrease since 2015 of 15.73%, then in 2019 it becomes 14.38%, far from the target set by the government at 17%, this is due to the lack of Indonesian UKM products interested in the global market. This causes the products of Indonesian SMEs to be unable to compete with SMEs of other countries in terms of export earnings. There are many factors that can cause this to happen, such as: lack of good standardization, many entrepreneurs only cater to the domestic market because they do not understand how to export, limited competent human resources and lack of access to financial institutions. Due to the limitations of the research model, especially those studying exports in developing countries, research using a quantitative approach with the SEM-PLS data analysis method is considered appropriate. The choice of the SEM-PLS method, because this research is predictive in nature, will of course be able to better represent the research model. In this study, there were 84 SMEs respondents who were registered with the Ministry of SMEs and Cooperatives. The results revealed that export market orientation had an effect as a mediating relationship between learning orientation and the performance of export SMEs, however, in an indirect relationship between entrepreneurial orientation and export performance, the mediating role of export market orientation not significant. This confirms that information related to export data needs good collaboration between company owners and employees.